PELATIHAN AKUTANSI SISTEM PEMBUKUAN DIGITAL DALAM PENERAPAN SIKLUS AKUTANSI PADA UMKM DI DESA GELELUNGI KABUPATEN ACEH TENGAH - Bambang Surahman; Elisa Khairani; Amru Bin AS; Sabri Sabri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this community service activity is to assist Micro, Small and Medium Enterprises (MSMEs) in making digital accounting books in implementing the accounting cycle for MSMEs by using a digital accounting application, namely "BukuKas". In addition, this community service activity can help students develop the knowledge and skills they have acquired in college and disseminate them to the general public. This service is carried out for MSME business owners in Gelelungi Village, Pegasing District, Central Aceh Regency.In the digital era like today, it is important for SMEs to optimize the use of technology. However, in reality there are still many MSMEs in Gelelungi Village, Pegasing District, Central Aceh District who do not optimize the use of technology that has developed in this era and still use manual bookkeeping that is neither systematic nor integrated.The implementation method in this community service activity is the lecture method and the practicum method directly. The results obtained in the digital bookkeeping system accounting training activities carried out have succeeded in helping MSME entrepreneurs in Gelelungi Village to carry out their business financial bookkeeping processes with digital openings easily, effectively, and efficient.